A new Drusinae species from the western Alps with comments on the subfamily and an updated key to filtering carnivore larvae of Drusinae species (Insecta: Trichoptera: Limnephilidae) - Vitecek, Simon; Graf, Wolfram; Martini, Jan; Zittra, Carina; Handschuh, Stephan; Kuhlmann, Hendrik C.; Vieira, Ariane; Hess, Monika; Heckes, Ullrich; Erzinger, Felicitas; Pauls, Steffen U.; Waringer, Johann (Zootaxa, 2020)
A new Drusinae species, Drusus katagelastos sp. nov., of the Drusus chapmani Species Complex, is described based on a male and associated larvae. Adult-larval association was achieved through DNA barcoding. The male of the new species differs from that of its congeners in the formation of the intermediate appendages and parameres. Information on the morphology of the larva is given, and important diagnostic features are discussed. In the context of filtering carnivore Drusinae, the larva of the new species can be separated from other filtering carnivore species by the dense cover of long translucent bristles within the frontal cavity surrounded by a circular corona of long bristles. Drusus katagelastos sp. nov. is known from only northwestern Italy (Piemonte).